Mobile genetic elements – mechanism and consequences of transposition - Wędrowski, Mateusz; Waśniowski, Paweł; Wędrowska, Ewelina; Golińska, Joanna; Piskorska, Elżbieta; Żukow, Walery (Journal of Education, Health and Sport, 2017)
Retrotransposons represent a significant part of the genome in eukaryote organisms. With DNA transposons, they belong to mobile genetic elements. There are two classes of transposons, DNA transposons and retrotransposons. Retrotransposons have three genes in their structure (gag, pol, env), responsible for the activation and encoding of structural proteins and envelope proteins. There is a group of retroelements without LTR (non-LTR). This group consists LINE (Long Interspersed Nuclear Elements) and SINE (Short Interspersed Nuclear Elements) sequences. LINE sequences represent 20% of human genetic material. Sequences of retrotransposons can move within the genome of a particular organism, occasionally subjected to replication as a result of enzyme activity, i.e. reverse transcriptase. The process of retro transposition is imperfect. These processes often cause mutation (most often: insertion, deletion), genetic instability, they contribute to the development of diseases on the genetic basis, including cancer. Retrotransposons are also used to analyze genetic variation as genetic markers.